Art and Artifice - Lucia Corrain (AN-ICON, 2023)
Art in general, more than other fields, appears to lie at the heart of immersivity. As argued by Oliver Grau, it is art that still deploys a considerable genealogy with examples that resonate with the immersivity as proposed in contemporaneity. It is the current immersivity that constructs “constellations” which, as Benjamin put it, dynamically enact “the history of art [as] the history of prophesies […] which can be written only starting from the point of view of an immediate present,” where “every present is determined by those images that are synchronous to it: each now is the now of a given knowability.” In the art history field, however, it is almost mandatory to re-evoke a fully mannerist ambience where “painting” creates – without the aid of particular instruments – the near-total immersion, acting fully on the passional dimension. The case in point is the Camera dei Giganti/Chamber of the Giants, made by Giulio Romano between 1532 and 1536 in Palazzo Te in Mantua. A stunning illusionist artifice that catapults the viewers into the heart of the ongoing event, to produce in them a sense of awe and estrangement beyond the “frame.”